The protective and pathogenic roles of IL-17 in viral infections: friend or foe? - Wen-Tao Ma; Xiao-Ting Yao; Qun Peng; De-Kun Chen (Open Biology, 2019)
Viral infections cause substantial human morbidity and mortality, and are a significant health burden worldwide. Following a viral infection, the host may initiate complex antiviral immune responses to antagonize viral invasion and replication. However, proinflammatory antiviral immune responses pose a great threat to the host if not properly held in check. Interleukin (IL)-17 is a pleiotropic cytokine participating in a variety of physiological and pathophysiological conditions, including tissue integrity maintenance, cancer progression, autoimmune disease development and, more intriguingly, infectious diseases. Abundant evidence suggests that while IL-17 plays a crucial role in enhancing effective antiviral immune responses, it may also promote and exacerbate virus-induced illnesses. Accumulated experimental and clinical evidence has broadened our understanding of the seemingly paradoxical role of IL-17 in viral infections and suggests that IL-17-targeted immunotherapy may be a promising therapeutic option. Herein, we summarize current knowledge regarding the protective and pathogenic roles of IL-17 in viral infections, with emphasis on underlying mechanisms. The various and critical roles of IL-17 in viral infections necessitate the development of therapeutic strategies that are uniquely tailored to both the infectious agent and the infection environment.